Comparison of Surgical Outcomes of Fistulotomy and Fistulectomy for the Management of Simple Low Fistula-In-ANO - Naeem Ghaffar, Mudassar Ali, Kamran Abbas (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study is done to compare the fistulotomy and fistulectomy for the treatment of fistulas in ano. This study is designed for the comparison of these surgical procedures to find out their results. Materials and methodology: this study was done at the surgery department of Sir Ganga Ram hospital Lahore during Jan 2021 to Dec 2021. 60 patients were included in this study and they were divided in two groups each of 30 participants. The group 1 patients were treated with fistulotomy while those of group 2 were selected for fistulectomy surgeries. The patients aged 20 years to 65 years were part of this study who were admitted to the department of surgery for planned fistulas operations. Before surgery Consent was taken from the patients themselves or by their close relatives. Exclusion criteria: Patients with recurrent fistulae. Fistulae with secondary tracts. Patients having different/ associated co-morbidities, like anal fissures, chronic colitis or hemorrhoids. Patients who refused to give consent for the study. Inclusion criteria: Low Fistulae-in-ano. Fistulae with single internal and external openings. Absence of secondary fistulous tracts. Results: 60 patients were included in this study. 30 of them were allocated in group 1 and were treated with fistulotomy and 30 who were the part of fistulectomy surgeries were taken group 2. Patients aging 20 to 60 years were the part of this study. Of group 1, 17 (56.6 %) were males and 13 (43.4%) were females and the mean average age was 39.9 + 10.11, among them, 9 (26.6%) were reported with pain and a total of 19 (53.3%) patients experienced pruritis. Of group 2, 40 + 12.2 was the mean age reported, among them 20 (66.66%) were males and 10 (33.33%) were females. Preoperatively 7 (23.33%) had pain issues and 21 (70.0%) complained of pruritus. The comparison of fistulotomy and fistulectomy surgeries is shown in table 2. The surgery time for fistulotomy was shorter than fistulectomy with a P value of 0.04. The hospital stay for group 1 patients was 2 days while 3 days for group 2 patients with no significant results. Wound healing time was quick in group 1 than group 2. While a gross difference in wound healing was noted as for the 1st group 3 weeks while 5 weeks for the 2nd. Group 1 patients complained less post operative pain than group 2. Conclusion: The conclusion is fistulotomy produces less post-operative pain than fistulectomy. Secondly wound healing was quick in fistulotomy than in fistulectomy. Keywords: Fistulotomy, Fistulectomy, Fistulae in ano.